2021
DOI: 10.1109/access.2021.3089358
|View full text |Cite
|
Sign up to set email alerts
|

Severity Assessment of Social Anxiety Disorder Using Deep Learning Models on Brain Effective Connectivity

Abstract: Neuroimaging investigations have proven that social anxiety disorder (SAD) is associated with aberrations in the connectivity of human brain functions.The assessment of the effective connectivity (EC) of the brain and its impact on the detection and medication of neurodegenerative pathophysiology is hence a crucial concern that needs to be addressed. Nevertheless, there are no clinically certain diagnostic biomarkers that can be linked to SAD. Therefore, investigating neural connectivity biomarkers of SAD base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…We expect to reveal neurobiological markers via the proposed analytical framework. In addition, among the existed studies [ 26 , 27 , 28 ], the highest classification accuracy between GAD and HC group, to our knowledge, is 93% with a deep learning model using task EEG signals. We also hope the proposed analysis framework could provide an effective and reliable GAD identification method to achieve better classification performance with machine learning models.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…We expect to reveal neurobiological markers via the proposed analytical framework. In addition, among the existed studies [ 26 , 27 , 28 ], the highest classification accuracy between GAD and HC group, to our knowledge, is 93% with a deep learning model using task EEG signals. We also hope the proposed analysis framework could provide an effective and reliable GAD identification method to achieve better classification performance with machine learning models.…”
Section: Introductionmentioning
confidence: 84%
“…Park et al reported their highest accuracy of 91.03% with elastic net classifier using resting-state EEG data [ 28 ]. Al-Ezzi et al achieved the accuracies of 92.86%, 92.86%, 96.43%, and 89.29% for severe, moderate, mild anxiety and HC by using a deep learning model (convolutional neural network + long short-term memory) with task-state EEG data, respectively [ 27 ]. Moreover, lower classification accuracies were reported using other modalities data [ 50 , 51 , 52 ], such as an accuracy of 87.4% with Self-Rating Anxiety Scale questionnaires data [ 12 ], and an accuracy of 86% with language-based features [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another future work is to use fuzzy methods [114,115] in epileptic seizure detection. In other future works, effective connectivity techniques may be used to diagnose epileptic seizures [116][117][118]; first, EEG signals are transformed into 2D images using effective connectivity methods. Then, these 2 D images are applied to different 2D deep learning networks.…”
Section: Discussion Conclusion and Future Workmentioning
confidence: 99%
“…We noted a majority of male participants in the studies, and more than half did not report the gender of their participants. Only two studies, including those by Al-Ezzi et al [ 25 ] and Perpetuini et al [ 26 ], used a sample size of more than 80 subjects. Four studies had around 55 to 57 subjects, three had between 20 and 40 subjects, and the rest had less than 20 subjects.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison between anxiety and anxiety disorder is one of the limitations of this review. Indeed, some studies [ 23 , 24 , 26 , 27 , 31 , 35 , 37 ], focus on detecting anxiety as an induced experience in danger, whereas others [ 15 , 16 , 19 , 25 , 26 , 28 , 32 ] aim to detect ADs subjects which need a timeline to be categorized, from health control.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%